Dear Theo: The Kerygmatic Intention and Claim of the Book of Acts - Minear, Paul Sevier 1906-2007 (1973)
When a community has risked its life by confessing its faith, when the cumulative pressures of existence in the world have made faith that dubious, an internal dialogue develops which can be called a dialogue between credulity and skepticism.